Factors influencing access to finance by SMEs in Mozambique: Case of SMEs in Maputo central business district - Hezron Mogaka Osano; Hilario Languitone (Journal of Innovation and Entrepreneurship, 2016)
SMEs play an important role in the economic development of Mozambique. Access to finance is important for the growth of SMEs. Thus, the purpose of the study was to establish the factors that influence access to finance by SMEs. The factors that were addressed included structure of financial sector, awareness of funding opportunities, collateral requirements, and small business support services. The target population was 2725 which comprised of 2075 staff of three Banks, namely BIM Bank, BCI Bank, and Standard Bank and 650 SMEs in Maputo Central Business District. The research focused on a sample size of 242 SMEs and 324 staff of the named Banks. Descriptive and inferential research design was used. Structured questionnaires were used to collect the primary data. The findings from the study were that there is a relationship between the structure of the financial sector and access to finance by SMEs; there is a relationship between awareness of funding and access to finance by SMEs; there is a relationship between collateral requirements and access to finance by SMEs; and there is a relationship between small business support and access to finance by SMEs. The study findings are significant since they would enable the government to come up with appropriate regulation, funding programs, and schemes toward improvement of access to finance by SMEs. This study concludes that small business support services should be provided to SMEs to improve access to finance and that there is a need for more funding programs and financial schemes to assist SMEs. It is further concluded that since information is concerned with funding opportunities by SMEs, then relevant information should be available and known to all players in the financial market.
Keywords: 650; Collateral requirements; Small business support services; Structure of financial sector; Awareness of funding opportunities; Access to finance